Cross layer energy location aware routing protocol (XELARP) for wireless multimedia sensor networks WMSNs - AlAmri, Ablah; Abdullah, Manal (International Journal of Engineering and Technology, 2018)
The field of sensor networks has expanded to include many special applications of monitoring environment. Wireless Multimedia Sensor Networks (WMSNs) are networks which have sophisticated sensor nodes with embedded audio and video sensors. These sensors are deployed in specific area to sense the surrounding physical environment and extract useful information. Then, it transmits these information to a sink node wirelessly. WMSNs have many challenges related to the limitations of node resources. Multimedia data includes audios, images and videos which are larger in volume than scalar data. Transmitting multimedia data have many strict constraints on the quality of services (QoS) in terms of energy, throughput and end-to-end delay. The layered architecture is not the best for WMSNs. Cross layered architecture is a new concept that combines several layers of TCP/IP architecture to enhance network’s QoS.